Faktor Makro Ekonomi Segi Moneter Terhadap Kinerja Indeks Saham Di Jakarta Islamic Index (JII) (Periode Januari 2010-Agustus 2015) - Dian Ayu Wulansari; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
Jakarta Islamic Index (JII) is one of Indonesia’s stock index in calculating the average price index of stocks for the type of stocks that meet the criteria of Shariah. One of the factors that influence is macroeconomic factors. This study aims to determine the effect of macroeconomic variables which consist of Inflation, Exchange Rate and M2 on the Jakarta Islamic Index (JII) with the observation period January 2010-August 2015. The data used is secondary data time series in the form of monthly data during the observation period January 2010-August 2015. The results showed that Exchange Rate and Money Supply (M2) have positively significant effect on the Jakarta Islamic Index (JII), whereas other variables such as Inflation is not significantly effect on the Jakarta Islamic Index (JII). While simultaneously the Inflation, Exchange Rate and Money Supply significant effect on the Jakarta Islamic Index (JII).